CIVILISATION DEVELOPMENT AND RELIGION IN MODERN JAPAN - Kim, Do-hyung (Journal of Dharma, 2022)
When considering the issue of equal and high-quality education for people, it is important to consider the quality of the knowledge propagated. 19th century Japan can be said to be a representative example of the diffusion of education and enlightened knowledge, improving people’s quality of life. At that time, Japanese Enlightenment intellectuals argued about what knowledge would help individual happiness and the country’s development. In particular, the debate over the relationship between religion and enlightenment knowledge was fierce. Some tried to use religion as a tool for accepting civilisation, while others argued that it was necessary to understand religion correctly for the development of civilisation. Representatively, Nishi Amane argued that correct knowledge could be established by separating and coexisting the area of knowledge and religion. He argued using traditional East Asian terms, and this case illustrates the activities of enlightenment intellectuals who pursued the policy of religion for civilisation development.